DAYA TERIMA DAN KANDUNGAN PROTEIN NUGGET KOMBINASI KACANG MERAH (Phaseolus Vulgaris. L) DAN HATI AYAM SEBAGAI PANGAN ALTERNATIF SUMBER PROTEIN UNTUK PENCEGAHAN STUNTING - Nandini, Astri Puspa; Fajri, Roifah; Yani, Ahmad (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background : Stunting become one of the nutritional problems in Indonesia. The prevalence of stunting in Indonesia reach to 30.8% based on the measurement results of H/A, the results consist of short and short 17.1% and very short 12.8%. Prevention can be done during preconception period with attention to protein intake, a protein source can obtained from red beans and chicken livers. Objective : To understand the acceptance difference nuggets of various ratios of red beans and chicken liver as an alternative food source of protein for the prevention of stunting and determine differences in protein content nuggets from various ratios of red beans and chicken liver as an alternative food source of protein for the prevention of stunting. Method : This study used a completely randomized design (CRD) with five treatments and three repetitions, the ratio of red beans and chicken livers ie, 90%: 10%, 70%: 30%, 50%: 50%, 30%:70%, 10%:90%. The acceptance of nuggets tested with hedonic test and the result were statistically analyzed using Mann Whitney and Kruskal Wallis. Protein content test conducted by the Kjeldahl method and the results were statistically analyzed using One Way anova and Duncan. Result : There are differences in aroma and color acceptance nuggets of various ratio of red beans and chicken livers. There are no significally difference in receptivity taste and texture nuggets of various ratios of red beans and chicken livers. There are differences in the protein content nuggets from various ratios of red bean and chicken liver. Conclusion : Results showed treatment nugget acceptance of 90%: 10%, 70%: 30%, 50%: 50% is the most preferred nuggets panelist. The highest protein level contained in the nugget with 50%:50% ratio of red beans and chicken liver the with 50 %:50% ratio of red beans and chicken liver